Identification of a Rare Mutation in the SRD5A2 Gene in an Iranian Family with Sex Development Disorder - Atiyeh Ataei; Peyman Eshraghi; Atiyeh Eslahi; Zeinab Khazaei; Masoome Alerasool; Sara Jamali; Faranak Ghadamyari; Majid Mojarrad (Journal of Sciences, Islamic Republic of Iran)
5 α-Reductase type 2 deficiency, caused by mutations in the SRD5A2 gene, leads to an autosomal recessive disorder of sex differentiation (DSD) in 46, XY persons.  A 2 years old female with ambiguous genitalia was referred to Genetic Foundation of Khorasan Razavi (GFKR), IRAN. Her secondary sex characteristics, level of sex hormones, the development of reproductive system and karyotype were assessed. Whole-exome sequencing (WES) was preformed to find the pathogenic genetic variations associated with ambiguous genitalia. Also, Sanger sequencing was used to verify the WES results in the patient. Segregation analysis was performed to confirm mutation in the parents and other relatives. Physical examination and ultrasonography data demonstrated that the patient have testis in the left labium majus and right groin but does not have a uterus or ovaries. Sex hormone examination revealed that hormone therapy was successful and the level of FSH, LH, testosterone, and dihydrotestostron (DHT) was 2.8 mlu/ml, 2.4 mlu/ml, 15ng/dl, 21pg/ml, respectively. Cytogenetic study showed 46XY compatible to normal male karyotype. According to WES result and Sanger sequencing a homozygote loss of function mutation (c.16C>T; p.Gln6Ter) in SRD5A2 has been detected. Segregation analysis confirmed the mutation in the family. Homozygote mutation in SRD5A2 is the main cause of disorders of sex development in this family.